PP-020 A prospective study of fibroblast growth factor 19 in patients with chronic diarrhoea and possible bile acid malabsorption. (23rd September 2015) - Pattni, S; Dew, T; Walters, J R F
Abstract : Introduction: Chronic diarrhoea resulting from excess bile acids in the colon ("bile acid malabsorption", BAM) is usually diagnosed by the selenium homocholic acid taurine (SeHCAT) test and responds to bile acid sequestrants. Other tests for BAM including serum levels of 7α-hydroxy-4-cholesten-3-one are not widely available. Our group suggested that disordered negative feedback inhibition by Fibroblast Growth Factor 19 (FGF19), produced by the ileum, of hepatic bile acid synthesis results in an excess of bile acids entering the colon, causing bile acid diarrhoea. We aim to examine further the role of FGF19 in a larger group of patients with chronic diarrhoea. Methods: 62 patients have been prospectively recruited with chronic diarrhoea. All patients had routine investigations for chronic diarrhoea to exclude other causes and all had SeHCAT tests. Three different patient groups were defined according to the diagnosis based on SeHCAT results: SeHCAT <15% and no other cause (primary BAM, n=21); SeHCAT <15% and secondary BAM (n=13); normal SeHCAT, >15% (n=28). All patient demographics and symptoms were recorded and fasting blood samples for FGF19 were collected and available in 54 patients. Serum FGF19 was quantified by ELISA using a commercially available kit. Results: Fasting FGF19 levels were significantly lower in patients with primary and secondary BAM compared with the chronic diarrhoea group with normal SeHCAT results (medians 160 vs 139 vs 276 pg/ml, p < 0.001). The majority of patients with primary BAM had SeHCAT retention of 5–10%. There was no significant difference in patient's age, gender, ethnicity, number of bowel movements per day or night, duration of diarrhoea, and stool consistency (Bristol Stool Chart) between the groups. The BMI was significantly higher in patients with abnormal SeHCAT values (27 vs 23.5, p<0.04). Faecal incontinence and urgency were more prevalent symptoms in these patients (50% vs 21%, p<0.03 and 94% vs 71%, p<0.03, respectively). Reported steatorrhoea, abdominal pain and bloating were features in both groups but no significant differences were noted. Conclusion: This study confirms that serum levels of an easily measurable hormone, FGF19, are significantly reduced in patients with bile acid diarrhoea, and are not affected by chronic diarrhoea per se. These patients also have a higher BMI. Other symptoms such as faecal incontinence, urgency abdominal pain, bloating and steatorrhoea are also common findings in these patients. These results provide further evidence that there is a disruption of a homeostatic mechanism in the control of bile acid synthesis with an overproduction of bile acids leading to chronic watery diarrhoea.